Permanent education, health promotions strategy and personal project reformulation - Urtubey, Elisa (2004)
The present paper intends to put forward some conclusions resulting from the research we have done with elderly people in the Elderly Permanent Education Program (PEPAM), pertaining to the Secretary Extension of the Faculty of Humanities and Education Sciences of the National University of La Plata, created in the year 1994 and the ad-hoc investigation carried out since the year 2003, called "Identifying process and the effects of new knowledge access in activities shared by elderly people in La Plata and greater La Plata". We shall illustrate the aforesaid through words and commentaries gathered during different moments of the task.